409. Rapid Development of a Multiplexed PCR Prototype Method that Offers a Syndromic Diagnostic Option by Integrating Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Detection with Twenty-One Other Common Respiratory Pathogens. (31st December 2020) - Spaulding, Usha; Antosch, Jeremiah; stone, Jessica; Robinson, Tanner; Halo, Kerrin; Kavetska, Iryna; Healy, Tyler; Taylor, Alex; Jones, Matthew; Todorov, Toma; Lu, Zhenmei; Cloud, Joann; et al.
Abstract: Background: The US Food and Drug Administration (FDA) has granted Emergency Use Authorization (EUA) for multiple PCR-based tests to aid in the diagnosis and containment of COVID-19. A vast majority of these tests detect only SARS-CoV-2 which causes symptoms similar to those caused by other respiratory pathogens. Hence, other etiologies or co-infections requiring a different therapy may be missed. The prototype BioFire® Respiratory Panel 2.1 (RP2.1) continues the syndromic approach of the FDA-cleared BioFire® Respiratory Panel 2 (RP2), to provide the ability to simultaneously detect 22 common respiratory pathogens, including SARS-CoV-2, from nasopharyngeal swab (NPS) specimens. The goal of this study was to rapidly develop a RP2.1 prototype that contains high-performing SARS-CoV-2 assays and maintains the performance of assays retained from RP2. Methods: Twelve assays designed for four SARS-CoV-2 genes were tested for compatibility with the RP2 assays and conditions. All retained RP2 assays were evaluated to verify established RP2 performance. The sensitivity of novel SARS-CoV-2 assays was estimated with nucleic acids at BioFire and contrived live virus NPS samples at MRIGlobal. Primer homology of SARS-CoV-2 assays to > 15, 000 SARS-CoV-2 genomes from accessible databases was assessed for in silico inclusivity Results: A prototype multiplexed PCR panel containing assays for 22 pathogens was developed in a 5-week period. Of the 12 SARS-CoV-2 assays, 7 were compatible with the RP2 conditions; 2 were selected for the prototype. No false positive results due to cross-reactivity with unintended analytes or non-specific amplification in negative samples were observed for any assays. All retained RP2 assays were detected at or near their established LoD. The SARS-CoV-2 LoD was estimated at 10 3 -10 2 genomes/mL with both nucleic acid and live virus spiked into NPS. Together, the assays are 100% inclusive for all 15, 370 complete SARS-CoV-2 genomes assessed in silico for reactivity. Conclusion: The results of this study indicate a strong potential for RP2.1 to serve as a sensitive comprehensive syndromic option to aid in the diagnosis of COVID-19 as well as respiratory syndromes caused by other pathogens, including co-infections. This study was performed with a test not cleared for diagnostic use. Disclosures: All Authors : No reported disclosures